Artificial weathering of bronze patinas - Selection of test conditions - Fontinha, I. R. (2010)
In this report, results of a study carried out with the objective of establishing the conditions for artificial weathering practice adequate to patinated bronze with applied conservation treatments are presented. The work developed is part of the research activities that have been carried out in the Metallic Materials Division for the European project ARTECH, integrated in the working group JRA1: Development and evaluation of new treatments for the conservation-restoration of outdoor stone and bronze monuments.